ALGORITHMIC GOVERNANCE DATA PROTECTION IN THE JUSTICE SYSTEM (ESMAT Magazine, 2026)
The paper examine data protection in Brazilian justice system under the hypothesis that the effectiveness of this fundamental right depends on a robust model of algorithmic governance, especially in the context of artificial intelligence expansion and the risks posed by “weapons of math destruction” in consumer relations and judicial activity. It analyzes the LGPD in dialogue with Consumer Law and Economic Constitucional Law, emphasizing human dignity, risk-based regulation and the institutional roles of controller, processor, data protection officer and the Nacional Data Protection Authority. Methodologically, it adopts an interdisciplinary approach, combining deductive-inductive reasorning with critical theory and Adorno’s negative dialectics, and connects theoretical reflection with empirical cases involving digital fraud, recent case law and sectoral regulation by BACEN, CNJ, the LGPD and the Digital Goverment Law. The study explores algorithmic governance in the Judiciary, focusing on AI risk categorization, impact assessments and structural challenges faced by judicial data protection officers. It concludes that responsible algorithmic governance requires network-based structures, transparency, diverity, continuos audits and preservation of judicial independence, so that automation expands access to justice without reinforcing inequalities. The work advocates a data protectios model grounded in a culture of compliance, redress for digital harms and the subordination of algorithms to the constitutional values of the Democratic Rule of Law.
Keywords: Algorithmic governance; Data Protection Law (LGPD); Artificial Intelligence (AI); Economic Constitution; Digital fraud